ANALISIS NILAI-NILAI PERSAHABATAN DALAM NOVEL HUJAN KARYA TERE LIYE - Lufita Lufita; Achmad Duwi Wijarnoko; Cintya Hidayatus Sholekah; Mohammad Kanzunndin (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This article analyzes the value of friendship in Tere Liye's novel Hujan. The study employs a qualitative research method using a literary sociology approach to explore how values such as loyalty, trust, support, mutual cooperation, and affection are reflected in the interactions between characters, particularly between the protagonists Lail and Esok. The analysis is based on the plot, characterization, setting, and themes of the novel. The findings indicate that Hujan not only presents an engaging fictional narrative but also conveys exemplary moral values to its readers. The depiction of friendship in the novel emphasizes the importance of honest relationships, mutual support, and trust.